Needs Analysis for Development of Interactive Electronic Textbooks Based (IETB) on Kvisoft Flipbook Maker Applications Integrated with Islamic Values - Emilia D.P.S; Saleh Hidayat; Indawan Indawan (Jurnal Pendidikan Biologi, 2022)
The use of technology and character building for students is an effort that can be made to improve the quality of education. Interactive Electronic Textbooks Based (IETB) that are integrated with Islamic values are able to empower students' brain abilities to think critically, creatively, and practice problem solving skills presented by teachers in class, so that learning objectives can be achieved properly. The purpose of this study is to analyze the development of IETB based on the Kvisoft Flipbook Maker application that integrates Islamic values in learning. The methods used in this research are field studies and literature studies. The research subjects were the principal, teachers and students of class XI majoring in science at SMA IT Bina Ilmi Palembang. Literature study was conducted by collecting various relevant sources. Meanwhile, the field study was obtained by going directly to the research location by interviewing the principal and class XI biology teacher as well as distributing needs questionnaires and conducting online learning observations. Based on a literature study, IETB based on the Kvisoft Flipbook Maker application can help students improve creative thinking skills and the integration of Islamic values in learning materials can improve critical thinking skills. The results of the field study found that SMA IT Bina Ilmi Palembang needed IETB to help teachers and students maximize learning and instill Islamic values according to the IISN curriculum used. This product can not only be used in Integrated Islamic Schools but can also be used in other Islamic based schools throughout Indonesia.